Pertussis in Children: Clinical and Epidemiological Features, the Possibilities of Vaccine Preventio - Y. A. Bogvilenе; G. P. Martynova; S. V. Evreimova; B. L. Komarova; A. V. Karasev (Эпидемиология и вакцинопрофилактика)
Relevance. Despite the specific immunization carried out, pertussis still has great medical and social significance for pediatricians, since it continues to remain a common bacterial infection, involving children of different age groups in the epidemic process. The lack of persistent immunity to whooping cough, combined with a high susceptibility index, contributes to an increase in the incidence among schoolchildren and adolescents, who are diagnosed only during epidemiological and laboratory examinations, and who, in most cases, serve as sources of infection for young children. Aim. To study the clinical and epidemiological features of whooping cough in children aged 0 to 14 years hospitalized in an infectious diseases hospital under conditions of mass vaccine prevention, as well as to identify the features of the disease in vaccinated people using the example of an outbreak of the disease in an organized group. Materials and methods. A retrospective analysis of 164 case histories of children diagnosed with Pertussis hospitalized in the infectious hospital of the Regional Interdistrict Children’s Clinical Hospital № 1 in Krasnoyarsk in 2015–2019, as well as 25 outpatient records of patients identified during the epidemiological investigation of the focus of infection in December 2019 was carried out. For the etiological interpretation of the diagnosis of whooping cough, a comprehensive laboratory examination was carried out using bacteriological, serological and molecular genetic research methods. Results. According to official statistics, in the Krasnoyarsk territory in 2019, among children with pertussis, patients aged 7 to 17 prevailed (38,7%). At the same time, in the age structure of patients hospitalized in a hospital, the primary importance was occupied by children of the first year of life, unvaccinated against this disease. Most of them were diagnosed with a moderate form of the disease with frequent development of complications from the respiratory and nervous systems. At the same time, among schoolchildren and adolescents, as a rule, who have received a completed course of vaccination, there is an atypical, erased course of the disease, while the difficulties of its diagnosis lead to a high incidence of pertussis in children of the first year of life who have not yet been protected by vaccination. Conclusions. Despite the high coverage of decreed groups with preventive vaccinations against whooping cough in the Krasnoyarsk territory, an assessment of the state of specific immunity based on the results of a serological survey conducted in 2019 revealed 50.6% of seronegative individuals already at the age of 3–4 years, which confirms the need to improve the schemes immunization against this disease; and inclusion of pertussis vaccination in the regional immunization schedule.